2013
DOI: 10.1039/c3cp53765j
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of mode- and bond-selectivity in vibrationally mediated reactions on surfaces

Abstract: On the origin of mode-and bond-selectivity in vibrationally mediated reactions on surfaces. Physical Chemistry Chemical Physics, 15, 47: 20545-20554, 2013 The experimental observations of vibrational mode-and bond-selective chemistry at the gas-surface interface indicate that energy redistribution within the reaction complex is not statistical on the timescale of reaction. Such behavior is a key prerequisite for efforts to use selective vibrational excitation to control chemistry at the technologically importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 76 publications
0
41
1
Order By: Relevance
“…The authors attributed the observed mode specificity to different degrees of C-H stretch vibrational amplitude localization in the dissociating bond (75). All these results demonstrate that the intramolecular vibrational energy redistribution (IVR) in the reactant molecule is slow on the several-hundred-femtosecond timescale of the reactive collision (76), in contradiction with the basic assumption of fast and complete IVR made by statistical rate theories (77-80). Killelea et al (81) were the first to demonstrate vibrational bond selectivity in the dissociative chemisorption of methane on Ni (111).…”
Section: Mode Specificitycontrasting
confidence: 50%
“…The authors attributed the observed mode specificity to different degrees of C-H stretch vibrational amplitude localization in the dissociating bond (75). All these results demonstrate that the intramolecular vibrational energy redistribution (IVR) in the reactant molecule is slow on the several-hundred-femtosecond timescale of the reactive collision (76), in contradiction with the basic assumption of fast and complete IVR made by statistical rate theories (77-80). Killelea et al (81) were the first to demonstrate vibrational bond selectivity in the dissociative chemisorption of methane on Ni (111).…”
Section: Mode Specificitycontrasting
confidence: 50%
“…No IVR can occur during the typically 100 μs flight time between laser preparation region and the approach to the surface in our apparatus because excitation by the cw-IR OPO (line width <1 MHz) prepares a single rovibrational eigenstate of the reactant molecule that has no time dependence and cannot undergo IVR. Once the reactant molecule enters the range of any molecule/surface interactions (d < 1 nm), surface-induced IVR 28 may start to occur during the remaining time needed for the molecule to reach the transition state. At the incident speed used in the experiments described here, this flight time within range of molecule/surface interactions is less than 500 fs.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This process is referred to as surface induced intramolecular vibrational redistribution (IVR). 8 The extent to which IVR occurs on the timescale of the collision will affect the relative reactivity of the different vibrational modes. The difference in vibrational efficacies demonstrates that the vibrational excitation remains localised in the initially prepared state, as opposed to being redistributed throughout the molecule through IVR.…”
Section: This Journal Is © the Royal Society Of Chemistry 2016mentioning
confidence: 99%
“…It should be pointed out that the single mode IR lasers used here prepare the reactant molecules in a single vibrational eigenstate 8 which undergoes no intramolecular vibrational redistribution (IVR) as long as the molecule travels in the molecular beam and is far (41 nm) from the target surface. In the harmonic oscillator approximation, these eigenstates are identical with the normal modes n i of the molecule.…”
Section: Reactant State Preparation By Infrared Pumpingmentioning
confidence: 99%